Strengthening Teachers’ Pedagogical Understanding of Love-Based Curriculum in Islamic Education Contexts - Rifadlin Amin; Samlan Ahmad; Muhammad Zein; Hujaima Konoras; Nur Rahmah Asnawi; Agus Agus (STIT Ahlussunnah Bukittinggi, 2026)
This study is motivated by the need for a more humanistic educational approach in responding to students’ social dynamics within Islamic education settings. Existing curricula tend to emphasize cognitive aspects and have not fully integrated affective dimensions based on values of compassion and love. This study aims to analyze the improvement of teachers’ understanding and pedagogical competence in implementing a love-based curriculum. A qualitative approach with a case study design was employed in this research. Data were collected through observations of training activities, analysis of teachers’ lesson plans, and documentation of limited implementation practices. The data were then analyzed using a descriptive-interpretive technique. The findings indicate an improvement in teachers’ conceptual understanding of the love-based curriculum, reflected in their ability to design more empathetic, participatory, and positive reinforcement-oriented learning activities. Teachers also demonstrated a shift toward more reflective pedagogical practices, emphasizing warm and meaningful educational relationships. These findings suggest that a love-based curriculum has the potential to serve as a strategic approach in strengthening character education and fostering more meaningful pedagogical relationships within Islamic education contexts.